Analisis Pemanfaatan Media Pembelajaran Berbasis TIK di Sekolah Dasar Negeri Pengadilan 5 Kota Bogor - L. Novita T. Windiyani S.S. Fauziah (Universitas Sebelas Maret, 2021)
This study aims to determine the use of ICT-based learning media at SDN Negeri 5 Bogor City. The approach used in this study is qualitative with descriptive analysis. Data sources consist of school principals, teachers, and students. Data collection techniques performed Data collection is done by observation (in the form of a checklist), interviews, and documentation. The researcher tested the validity of the data by means of further observations, and triangulation of data. The results showed that the six aspects studied were (1) teacher knowledge of low category ICT-based media, (2) ability to use medium-based ICT media, (3) ability to create low-category ICT-based media, (4) relevance of media-based use ICT with low category learning objectives, (5) relevance of the use of ICT-based media with medium category learning material, and (6) relevance to the characteristics of high category students. Based on the results of research that has been carried out it can be concluded that the use of ICT-based learning media in SD Negeri Pengadialn 5, Bogor City is in the low category. Thus it is necessary for teachers and schools to conduct training in order to increase knowledge about technology-based media in accordance with the times.Kata kunci: Media Pembelajaran dan TIK